Locked and (Un)-Loaded Discussions: A Pediatric Resident Safe Firearm Storage Counseling Curriculum - Clary, Cody (MedEdPORTAL, 2020)
INTRODUCTION: Firearm-related fatalities are a public health crisis. Despite recognizing the vital nature of counseling parents/caregivers regarding firearm safety, residents remain uncomfortable asking patients about the presence of firearms in homes and discussing American Academy of Pediatrics recommendations regarding safe firearm storage. METHODS: We designed an interactive curriculum to improve pediatric resident knowledge, skills, attitudes, and behavior regarding counseling families about safe firearm storage. Components of the curriculum included a didactic session, a hands-on experience to better understand the parts of a firearm and its relevant storage/safety devices, and role-playing scenarios. RESULTS: The curriculum was delivered to 53 pediatric residents in two different residency programs. A statistically significant improvement in knowledge and skills related to safe firearm storage counseling was demonstrated in both settings. Furthermore, a statistically significant change in counseling behavior was noted among one resident group. Curriculum evaluation revealed overwhelmingly positive learner responses. DISCUSSION: An adaptable interactive safe firearm storage counseling curriculum was well received by pediatric residents and improved resident knowledge and skills, resulting in an increase in safe firearm storage counseling discussions with families.